2016
DOI: 10.1098/rsta.2015.0294
|View full text |Cite
|
Sign up to set email alerts
|

The oceanic budgets of nickel and zinc isotopes: the importance of sulfidic environments as illustrated by the Black Sea

Abstract: Isotopic data collected to date as part of the GEOTRACES and other programmes show that the oceanic dissolved pool is isotopically heavy relative to the inputs for zinc (Zn) and nickel (Ni). All Zn sinks measured until recently, and the only output yet measured for Ni, are isotopically heavier than the dissolved pool. This would require either a non-steady-state ocean or other unidentified sinks. Recently, isotopically light Zn has been measured in organic carbon-rich sediments from productive upwelling margin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
104
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 81 publications
(213 reference statements)
9
104
1
Order By: Relevance
“…Sulfides can also capture organic‐delivered Zn released during biomass decay within sedimentary porewaters, a process that would drive the signature toward lighter δ 66 Zn values typical of organic matter. Zinc sulfide formation can also be associated with a negative isotope fractionation (Vance et al., ). However, near‐quantitative Zn drawdown, due to much lower Zn concentration relative to that of H 2 S, as is typical in sulfide‐rich water columns and porewaters (e.g., Tankéré et al., ), is likely to mute isotope fractionation tied to aqueous Zn speciation or kinetic effects during sulfide precipitation (John, Kunzmann, Townsend, & Rosenberg, ; Vance et al., ).…”
Section: Global Zinc Isotope Mass Balance: Organic Biomass a Large Amentioning
confidence: 99%
“…Sulfides can also capture organic‐delivered Zn released during biomass decay within sedimentary porewaters, a process that would drive the signature toward lighter δ 66 Zn values typical of organic matter. Zinc sulfide formation can also be associated with a negative isotope fractionation (Vance et al., ). However, near‐quantitative Zn drawdown, due to much lower Zn concentration relative to that of H 2 S, as is typical in sulfide‐rich water columns and porewaters (e.g., Tankéré et al., ), is likely to mute isotope fractionation tied to aqueous Zn speciation or kinetic effects during sulfide precipitation (John, Kunzmann, Townsend, & Rosenberg, ; Vance et al., ).…”
Section: Global Zinc Isotope Mass Balance: Organic Biomass a Large Amentioning
confidence: 99%
“…Recent experiments and natural studies have also reported the same fractionation direction, with Δ 66 Zn sulfide‐solution = ~−0.3‰ (Archer & Vance, ; Jamieson‐Hanes et al, ; Veeramani et al, ). This potential mechanism has been widely used to explain lower δ 66 Zn values in sphalerites (Veeramani et al, ) and organic‐rich shales (Little et al, ; Vance et al, ). If Zn precipitation in deep seawater is dominated by Zn sulfides, then the Zn isotope composition of the Zn sulfide fraction should be equal to or lighter than that of the water column.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the deep‐water Wuhe section may have been deposited under ferruginous conditions with intermittent euxinic conditions (Han & Fan, ; Sahoo et al, ), where the dissolved Zn could be scavenged from seawater by H 2 S that was reduced from dissolved sulfate. If the dissolved Zn was quantitatively precipitated as sulfide under sulfidic condition, the sediments would be isotopically similar to seawater‐derived Zn (Tang et al, ; Vance et al, ). For example, the euxinic sediments in the Black Sea record the Zn isotopic signature of the deep ocean, which has been attributed to the quantitative removal of Zn from the water column by Zn sulfide precipitation (Vance et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations